2005
DOI: 10.2320/matertrans.46.1255
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of Multiplier Effects of Helium Plasma and Neutron Irradiation on Microstructural Evolution in Tungsten

Abstract: Plasma-facing and high heat flux materials in a fusion reactor suffer two types of damage: displacement damage caused mainly by highenergy neutrons and surface damage, such as erosion, sputtering, and blistering, caused by hydrogen and helium plasma. Usually, these two kinds of damage are investigated separately. In the present study, multiplier effects of helium plasma and neutron irradiation on microstructural evolution in tungsten were investigated using computer simulations based on a rate theory. Neutron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These results suggest that injected helium interacts with lattice defects produced by the neutron irradiation in the fusion reactor. Recent simulation results based on a simple model using rate theory, where the diffusion of helium and the point defects produced by neutron irradiation were considered, agreed with the suggestion and indicated that helium was trapped by vacancies to form helium-vacancy clusters in tungsten even in the region deeper than the range of helium [7]. In order to gain a better understanding of the performance of tungsten under the ITER condition, in the present work, we focused on the damage evolution in tungsten with simultaneous irradiation by helium and neutrons.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…These results suggest that injected helium interacts with lattice defects produced by the neutron irradiation in the fusion reactor. Recent simulation results based on a simple model using rate theory, where the diffusion of helium and the point defects produced by neutron irradiation were considered, agreed with the suggestion and indicated that helium was trapped by vacancies to form helium-vacancy clusters in tungsten even in the region deeper than the range of helium [7]. In order to gain a better understanding of the performance of tungsten under the ITER condition, in the present work, we focused on the damage evolution in tungsten with simultaneous irradiation by helium and neutrons.…”
Section: Introductionsupporting
confidence: 63%
“…In the case of 1 keV-helium irradiation, defect production by the helium is taken into account, which is different from the model used in Ref. [7], but there are no displacement events for the 30 eV-helium irradiation. In contrast to the uniform damage produced by neutron irradiation, injected helium and associated damage is located close to the incident surface.…”
Section: Outline Of the Modelmentioning
confidence: 99%
“…Tritium, interstitials, vacancies and their clusters with tritium could migrate freely in the matrix, and their concentrations at both surfaces are zero at all times. The time evolution of the concentration of point defects, defect clusters and tritium were calculated using dynamic rate theory [6][7][8] with the following assumptions:…”
Section: Outline Of the Modelmentioning
confidence: 99%
“…Because of its extremely low solubility in materials, helium precipitates into bubbles by absorbing vacancies, which deteriorate the mechanical properties of materials [1][2][3][4][5]. The interaction between He and irradiation-induced defects, especially vacancies, has been investigated [6,7]. A molecular dynamics study [8] has shown that a single interstitial He atom can easily migrate through a perfect a-iron lattice owing to its small migration energy of 0.08 eV.…”
Section: Introductionmentioning
confidence: 98%